Karakteristik Ikan Cakalang (Katsuwonus pelamis) Asap Pada Waktu Pengasapan Berbeda Menggunakan Alat Pengasapan Semi Modern - Saharu, Moh. Afandi H; Sulistijowati, Rieny; Suherman, Sutianto Pratama (Universitas Negeri Gorontalo, 2025)
The present rescarch aimed to analyze the sensory characteristics and moisture content of smoked skipjack tuna using modern smoking equipment at different smoking times. The research method used was an experimental research method with two replications. Besides, the treatment factor was the length of smoking times which consisted of three levels: one hour, three hours, and five hours. The moisture content test was done through non-factorial completely randomized design analysis and Duncan’s multiple range test, In contrast, the sensory quality test was analyzed descriptively using the Rasch Model method. The findings revealed that different lengths of smoking had a significant effect (p 0,05) on the moisture content of smoked skipjack tuna. Based on the results of the Rasch Model analysis, it was found that the panelis preferred the sensory quality of smoked fish in treatment B (three hours).